PENGARUH CITRA MEREK DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA - HABIR, HASTUTI (Fakultas Ekonomi Universitas Tadulako, 2018)
This research aims to find out and analyze the effect of brand image and word of mouth, either simultaneously or partially on the decision of purchasing Yamaha motorcycle in Bungku Tengah of Morowali Regency. This was a descriptive research with population of consumers of yamaha motorcycle in Bungku Tengah of Morowali Regency. Sample used was random sampling, in which 91 people selected as the sample. Data collection was questionnaire and it was analyzed using multiple linear regression analysis.The research result reveals that significant probability value of brand image variable (0.002) < (0.05) so the brand image variable has a significant effect on the decision of purchasing, significant probability value of word of mouth (0.087) > (0.05) so the word of mouth variable has no effect on the decision of purchasing. It means the brand image variable partially has a significant effect on decision of purchasing; however, word of mouth variable partially has no effect on kdecision of purchasing.